Penerapan Pendekatan Kontekstual untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa Sekolah Dasar - Utami, Nanda Dwi (Indonesian Journal Publisher, 2024)
The purpose of this research is to analyze issues in the implementation of innovative learning media in science education at elementary schools through the 2013 Curriculum and the Merdeka Curriculum. The subjects of this study are fifth-grade teachers in public elementary schools located in Jakarta. The research employs a qualitative descriptive method, using techniques such as interviews and observations. The results of the study show that the learning media plays a crucial role in the implementation of learning activities in the classroom, as well as in enhancing students' motivation to learn and their interest in the subject.